Empowering Parents of PPWNI Klang Selangor Malaysia Students Through Recycle and Access Market Activities - Devinra Devinra; Oman Hadiana; Tio Heriyana; Hana Astria Nur; Casnan (ABDIMAS: Jurnal Pengabdian Masyarakat, 2023)
Some parents of students who are in PPWNI Klang Selangor Malaysia school to accompany or take their children to study, it seems that their activities are too monotonous, such as dropping off and waiting for their children to study at PPWNI Klang Selangor Malaysia school, really something that needs action. Some can be seen just waiting while buying snacks or even social gatherings between parents of students. Moreover, their existence is clustered and a little disturbing because they chat a lot with other students' parents. This condition can be sought so that the activity of waiting for his child to learn is not boring or disturbing his child who is studying and of course can be worth ringgit for them. Therefore, the service team held training in making several creations from bottle waste that had never been done before. These creations are in the form of handicrafts from bottle waste that are formed into various kinds of objects such as piggy banks, pencil holders, flower vases, etc. This creation activity can be done anytime and anywhere, the purpose of this community service activity is to (1) utilize free time, (2) reduce environmental waste, and (3) increase market access knowledge of parents of PPWNI Klang Selangor Malaysia school students. This method of community service activities is carried out with lectures, and simulations. The stages passed include field surveys, socialization, notification to parents, implementation of activities, and evaluation of training activities. Through PKM activities, parents are expected to develop their creativity optimally and help improve the family economy through entrepreneurship